Development of Swept-sine Excitation Control Method to Minimize the FRF Measurement Error - Yanto, Asmara; Abidin, Zainal (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
Shaker excitation in FRF (Frequency Response Function) measurement of a testing system can be controlled by using swept-sine signal source in a signal generator and it is called with swept-sine excitation. FRF’s magnitude error of the system which is obtained from the FRF measurement using swept-sine excitation depends on swept function of swept-sine signal. In this paper, swept-sinesignals using linear and S535 swept functions have been simulated to controlling swept-sine excitation in the FRF measurement of SDOF (Single Degree of Freedom) system. Linear swept is swept function of swept-sine signal which is often used in the FRF measurement and S535swept is a swept function has been developed in this paper. Based on simulation results, the FRF’s magnitude error at system’s resonant frequency which was obtained from the FRF measurement using linear swept-sine excitation can be minimized by redoing the FRF measurement using S535 swept-sine excitation.